Arterial Properties as Determinants of Left Ventricular Mass and Fibrosis in Severe Aortic Stenosis: Findings From ACRIN PA 4008. Issue 1 (8th January 2019) - Chirinos, Julio A.; Akers, Scott R.; Schelbert, Erik; Snyder, Bradley S.; Witschey, Walter R.; Jacob, Ron M.; Jamis‐Dow, Carlos; Ansari, Bilal; Lee, Jonathan; Segers, Patrick; Schnall, Mitchell; Cavalcante, João L.
Abstract : Background: The role of arterial load in severe aortic stenosis is increasingly recognized. However, patterns of pulsatile load and their implications in this population are unknown. We aimed to assess the relationship between the arterial properties and both (1) left ventricular remodeling and fibrosis and (2) the clinical course of patients with severe aortic stenosis undergoing aortic valve replacement (AVR). Methods and Results: We enrolled 38 participants with symptomatic severe aortic stenosis scheduled to undergo surgical AVR. Aortic root characteristic impedance, wave reflections parameters (reflection magnitude, reflected wave transit time), and myocardial extracellular mass were measured with cardiac magnetic resonance imaging and arterial tonometry Cardiac magnetic resonance imaging was repeated at 6 months in 30 participants. A reduction in cellular mass (133.6 versus 113.9 g; P =0.002) but not extracellular mass (42.3 versus 40.6 g; P =0.67) was seen after AVR. Participants with higher extracellular mass exhibited greater reflection magnitude (0.68 versus 0.54; P =0.006) and lower aortic root characteristic impedance (56.3 versus 96.9 dynes/s per cm 5 ; P =0.006). Reflection magnitude was a significant predictor of smaller improvement in the quality of life (Kansas City Cardiomyopathy Questionnaire score) after AVR ( R =−0.51; P =0.0026). The 6‐minute walk distance at 6 months after AVR was positively correlated with the reflected wave transit time ( R =0.52; P =0.01). Conclusions: Consistent with animal studies, arterial wave reflections are associated with interstitial volume expansion in severe aortic stenosis and predict a smaller improvement in quality of life following AVR. Future trials should assess whether wave reflections represent a potential therapeutic target to mitigate myocardial interstitial remodeling and to improve the clinical status of this patient population.